2013
DOI: 10.1182/blood-2013-06-510586
|View full text |Cite
|
Sign up to set email alerts
|

Plasma microRNA signature as a noninvasive biomarker for acute graft-versus-host disease

Abstract: • Identification of a miRNA panel as a biomarker for the diagnosis, prognosis, and prediction of acute graft-versus-host disease.Acute graft-versus-host disease (aGVHD) is the leading cause of morbidity and mortality after allogeneic hematopoietic cell transplantation (HCT). Approximately 35% to 50% of HCT recipients develop aGVHD; however, there are no validated diagnostic and predictive blood biomarkers for aGVHD in clinical use. Here, we show that plasma samples from aGVHD patients have a distinct microRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
139
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 120 publications
(145 citation statements)
references
References 44 publications
2
139
3
1
Order By: Relevance
“…Given the involvement of the skin and immune system in GvHD, the role of miRNAs in the pathogenesis of GvHD has been hypothesized. Xiao et al (59) provided supporting evidence for this hypothesis, and demonstrated that the plasma levels of miR-423, miR-199a-3p, miR-93* and miR-377 were significantly upregulated in patients with acute GvHD. In another study, Atarod and Dickinson (6) used Ingenuity Pathway Analysis to further investigate the interactions between the GvHD signalling pathway and miRNAs.…”
Section: Graft-versus-host Diseasesmentioning
confidence: 75%
“…Given the involvement of the skin and immune system in GvHD, the role of miRNAs in the pathogenesis of GvHD has been hypothesized. Xiao et al (59) provided supporting evidence for this hypothesis, and demonstrated that the plasma levels of miR-423, miR-199a-3p, miR-93* and miR-377 were significantly upregulated in patients with acute GvHD. In another study, Atarod and Dickinson (6) used Ingenuity Pathway Analysis to further investigate the interactions between the GvHD signalling pathway and miRNAs.…”
Section: Graft-versus-host Diseasesmentioning
confidence: 75%
“…Further investigations into pre-transplant risk assessment could also include other potential predictors such as mRNA and microRNA expression. 60 …”
Section: Discussionmentioning
confidence: 99%
“…A clinical trial to further establish the significance of miR-155 in aGVHD is currently ongoing (ClinicalTrials.gov Identifier: NCT01521039). In addition, a group of miRs (miR-423, miR-199-3p, miR-93*, and miR-377) [6], miR-100 [7], miR-34a [8], and miR-146a [9] has also been identified to play an important role in the process of aGVHD after allo-HSCT. Atarod et al identified eight miRs (miR-146a, miR-155, miR-515, miR-346, miR-143, miR-373, miR-310, and miR-29) which could target different molecules in the GVHD signaling pathway [10].…”
Section: Introductionmentioning
confidence: 98%